Flexible virtual capacitance control strategy for a DC microgrid with multiple constraints. Issue 17 (22nd February 2021) - Meng, Jianhui; Zhang, Yun; Wang, Yi; Song, Meiqi; Zhao, Pengfei; Liu, Bao
Abstract : In a DC microgrid, the anti‐interference ability of bus voltage can easily become vulnerable due to low inertia caused by a large number of power electronic converters. This has already challenged the system stability and practicability in DC girds. In this study, a flexible virtual capacitance (FVC) control strategy with multiple constraints (MCs) is proposed to guarantee the security and stability of the DC microgrid, where the system stability, dynamic characteristics, actual operation requirements and realisability are considered as MCs. The FVC controller, which mainly modifies the reference current in voltage source converter by flexibly regulating virtual capacitance value, is given to provide inertial support and improve voltage quality. The stable operating boundary calculation based on small signal model and key control parameters design are further introduced into the control loop. This can ameliorate the dynamic response of the microgrid and obtain the better engineering practicability. Finally, experiment tests on a controller‐level hardware‐in‐the‐loop simulation platform are carried out to verify the validity of the proposed strategy.